2006
DOI: 10.1002/jnr.20955
|View full text |Cite
|
Sign up to set email alerts
|

Cellular composition of long‐term human spinal cord‐ and forebrain‐derived neurosphere cultures

Abstract: In vitro expanded neural precursor cells (NPCs) may provide a stable source for cell therapy. In search of the optimal cell source for spinal cord repair, we investigated influences of gestational age, regional heterogeneity, and long-term in vitro propagation. The cellular content of neurosphere cultures prior to and after in vitro differentiation was studied by immunocytochemistry and flow cytometry. Human forebrain and spinal cord NPCs deriving from first-trimester tissue were cultured as neurospheres in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 31 publications
(49 reference statements)
7
44
1
Order By: Relevance
“…2A) (Fig. 2C), which encodes the cell surface antigen CD133, expressed in up to 40% of cultured NSC (Piao et al 2006;Sun et al 2009). All analyzed PROM1 sequences had low or no methylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A) (Fig. 2C), which encodes the cell surface antigen CD133, expressed in up to 40% of cultured NSC (Piao et al 2006;Sun et al 2009). All analyzed PROM1 sequences had low or no methylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with earlier investigations which have shown that NSCs derived from human spinal cord tissue demonstrate a reduced capacity to generate the oligodendrocytic phenotype and as a consequence an increase in the number of GFAP expressing cells with passage (Chandran et al, 2004;Quinn et al, 1999;Svendsen et al, 1998). Comparing long term cultures of human NSCs derived from brain to those from the corresponding spinal cord, Piao et al found that the brain derived neurospheres generated consistent numbers of neural phenotypes while the spinal cord derived neurospheres showed a significant decrease in bIII-tubulin 1 and increase in GFAP 1 cells by passage 5 and at passage 10 the O4 1 cells only equated to 0.5% of the total cell numbers (Piao et al, 2006). Other studies of neurospheres derived from fetal and embryonic human spinal cord have found no evidence for the oligodendrocytic phenotype after differentiation in vitro (Barami et al, 2001a,b;Iwanami et al, 2005;Walder and Ferretti, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…However, previous in vitro studies showed that subjecting hNS/PCs to multiple passages for up to 300 days in vitro (DIV) reduces their growth rate and alters their neurogenic potential (Caldwell et al, 2001;Kanemura et al, 2002;Piao et al, 2006;Wright et al, 2006;Anderson et al, 2007). Neither the proliferative and differentiation properties nor the in vivo dynamics have been reported for hNS/ PCs cultured for longer than 300 DIV.…”
mentioning
confidence: 91%